Acupuncture Combined with Kinesitherapy in Treating 40 Cases of Senile Stroke Patients with Sleep Disorder - Jiachun LU; Xingang BAI; Xinghua LEI; Xingjuan XIONG; Yan CHEN; Quan WEN; Bibo LU; Min HE; Wenchun WANG; Anren ZHANG (康复学报)
Objective:To observe the curative effects of acupuncture combined with kinesitherapy for the treatment of sleep disorder in senile stroke patients.Methods:80 sleep disorder in senile stroke patients were randomly assigned to treatment group (n=40) and control group (n=40). The treatment group was treated with acupuncture and kinesitherapy, and the control group received estazolam tablets for four weeks. The pittsburgh sleep quality index (PSQI), self-rating scale of sleep (SRSS), TCM symptom scale, barthel index (BI) and quality of life (QOL) were examined before and after treatment.Results:The difference-value of PSQI, SRSS, TCM symptom scale, BI and QOL in the treatment group before and after treatment was higher respectively than those in the control groups, and the differences were significant (P<0.01).Conclusion:Acupuncture combined with kinesitherapy can improve the quality of sleep, TCM symptom, activities of daily living and QOL of senile stroke patients, and its effect is better than that of western medicine. Acupuncture combined with kinesitherapy may be used as an effective method to treat sleep disorder in senile stroke patients.